Demystifying the impact of self-indulgence and self-control on customer-employee rapport and customer happiness - Fatima, J.; Sharma, Piyush; Di Mascio, R. (Elsevier, 2020)
Past research mostly ignores the link between customers' purchase orientations and their engagement with frontline service employees. This paper addresses this gap by using socio-emotional selectivity theory to investigate the effects of customers’ self-indulgence/control on their rapport building efforts with frontline service employees and on their own happiness. It also explores the moderating effects of age, gender and shopping day on the impact of self-indulgence/control on happiness. Data from 252 Australian customers shows that self-control has no significant influence on rapport or happiness while rapport and self-indulgence positively affect happiness. Finally, all the moderating effects only find partial support.